Instrumentos económicos basados en mercados para la conservación de la biodiversidad y los servicios ecosistémicos en latinoamérica: ¿panacea o rueda cuadrada? - Aguiar, S., Camba Sans, G., Paruelo, J. (My University, 2017)
The perception that the strategies carried out by governments for biodiversity conservation and ecosystem services provision are ineffective or insuficient, led to diverse new alternatives based on economic instruments driven by both private actors (fundamentally NGO&rsquos) and governments. Some of these instruments seek to internalize a positive externality by compensating the ecosystem service (ES) provider for the costs incurred in ensuring its provision. Currently, there is no consensus on the strengths and weaknesses of the market based economic instruments for nature conservation (MBEINC), and most of this debate has taken place in a theoretical arena. Thus, the need for empirical assessment is essential. The objective of this work was to characterize 60 projects, which included MBEINC, in Latin America in terms of their effectiveness and social equity, and the relation of them with diverse economic, political and institutional characteristics. Through this we seek to explore whether there are synergies or tradeoffs between environmental and social objectives, and determine which characteristics determine that the projects are more successful with respect to these objectives. 43% of the projects were effective in terms of their environmental objectives, while approximately 17% were socially equitable. The relationship between efectiveness and social equity was not statistically significant, indicating that there are no synergies or tradeofs between them. In general, both effectiveness and social equity were not significantly associated with any of the characteristics surveyed. This implies that there is no single institutional arrangement to ensure the positive outcomes of this type of mechanism. Our results suggest that there is insuficient evidence of the advantages of MBEINC to conserve biodiversity and ES in an effective and socially equitable manner in Latin America.
Keywords: payment for ecosystem services, equity, effectiveness, South America, Central America, PES